EFEKTIVITAS SANKSI PIDANA PAJAK DALAM UNDANG-UNDANG NOMOR 28 TAHUN 2007 TENTANG KETENTUAN UMUM DAN TATA CARA PERPAJAKAN (Studi di Pengadilan Pajak Jakarta) - Tri Wibowo (Jurnal Dinamika Hukum, 2009)
One effort of realizing independence of nation in defrayal of development is find the source of fund that coming from tax. But, there are behavior of tax evasion that manipulated by legal subject and object of tax for to get thrift of tax by doing contempt of court (unlawful), and manipulate the tax is coherent virus (inherent) in each tax system that applying in every jurisdiction.  Based on research result, applying of sanction in the case of manipulate of tax is not yet effective, because not all that order in the norm did, for example bookkeeping’s not true and not yet had NPWP. Therefore, the policy formulation of crime sanctions in Law Taxation and also there must be support society and from government enforcers, so application of sanction of crime in taxation area can effectively did it. Kata Kunci : Pajak, Penggelapan Pajak, efektivitas sanksi pidana